CSF‐1 receptor‐mediated differentiation of a new type of monocytic cell with B cell‐stimulating activity: its selective dependence on IL‐34. Issue 1 (19th September 2013) - Yamane, Fumihiro; Nishikawa, Yumiko; Matsui, Kazue; Asakura, Miki; Iwasaki, Eriko; Watanabe, Koji; Tanimoto, Hikaru; Sano, Hiroki; Fujiwara, Yuki; Stanley, E. Richard; Kanayama, Naoki; Mabbott, Neil A.; et al.
Abstract : Occurrence of a CSF‐1 receptor‐dependent monocyte differentiation process driven by IL‐34, but not CSF‐1. Abstract : With the use of a mouse FDC line, FL‐Y, we have been analyzing roles for FDCs in controlling B cell fate in GCs. Beside these regulatory functions, we fortuitously found that FL‐Y cells induced a new type of CD11b + monocytic cells (F4/80 +, Gr‐1 −, Ly6C −, I‐A/E −/lo, CD11c −, CD115 +, CXCR4 +, CCR2 +, CX3 CR1 − ) when cultured with a Lin − c‐kit + population from mouse spleen cells. The developed CD11b + cells shared a similar gene‐expression profile to mononuclear phagocytes and were designated as FDMCs. Here, we describe characteristic immunological functions and the induction mechanism of FDMCs. Proliferation of anti‐CD40 antibody‐stimulated B cells was markedly accelerated in the presence of FDMCs. In addition, the FDMC‐activated B cells efficiently acquired GC B cell‐associated markers (Fas and GL‐7). We observed an increase of FDMC‐like cells in mice after immunization. On the other hand, FL‐Y cells were found to produce CSF‐1 as well as IL‐34, both of which are known to induce development of macrophages and monocytes by binding to the common receptor, CSF‐1R, expressed on the progenitors. However, we show that FL‐Y‐derived IL‐34, but not CSF‐1, was selectively responsible for FDMC generation using neutralizing antibodies and RNAi. We also confirmed that FDMC generation was strictly dependent on CSF‐1R. To our knowledge, a CSF‐1R‐mediated differentiation process that is intrinsically specific for IL‐34 has not been reported. Our results provide new insights into understanding the diversity of IL‐34 and CSF‐1 signaling pathways through CSF‐1R.